Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/smll.202100438
|View full text |Cite
|
Sign up to set email alerts
|

A Transparent Nanopatterned Chemiresistor: Visible‐Light Plasmonic Sensor for Trace‐Level NO2 Detection at Room Temperature

Abstract: The highly selective detection of trace gases using transparent sensors at room temperature remains challenging. Herein, transparent nanopatterned chemiresistors composed of aligned 1D Au–SnO2 nanofibers, which can detect toxic NO2 gas at room temperature under visible light illumination is reported. Ten straight Au–SnO2 nanofibers are patterned on a glass substrate with transparent electrodes assisted by direct‐write, near‐field electrospinning, whose extremely low coverage of sensing materials (≈0.3%) lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Figure f depicts light absorption behavior of InSe and Au-InSe. Consistent with the previous report, the high absorption ability of InSe ranges from UV to near-infrared regions. , A new absorption peak located at ∼550 nm in Au-InSe can be contributed by the localized surface plasmon resonance (LSPR) of Au NPs . Morphologies of sensing films are displayed in Figure S3c–e.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figure f depicts light absorption behavior of InSe and Au-InSe. Consistent with the previous report, the high absorption ability of InSe ranges from UV to near-infrared regions. , A new absorption peak located at ∼550 nm in Au-InSe can be contributed by the localized surface plasmon resonance (LSPR) of Au NPs . Morphologies of sensing films are displayed in Figure S3c–e.…”
Section: Resultssupporting
confidence: 89%
“…Figure f shows that the sensing responses to both gases are decent, and the maximum responses were obtained at 20 and 10 wt % of Au loading toward NO 2 and NH 3 , respectively. The reduced response at high Au concentration is likely to do with the enlargement of Au NPs that possibly induces attenuated LSPR, spillover effect, etc . Different from the other sensors’ behavior, 40 wt % Au-InSe/IDEs displayed a positive response to NH 3 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, Kim et al reported the detection of NO 2 gas by a one-dimensional Au-SnO 2 nanofiber sensor under visible light at RT (Lim et al, 2021). The sensor shows a high degree of selectivity, sensitivity and repeatability in response to NO 2 at sub ppm levels.…”
Section: Gas Sensors Based On Noble Metal Doping Nanostructurementioning
confidence: 99%
“…Tremendous developments of the modern industry and smart city have occurred and dramatically changed our life. As the key sensing node of Internet of Things (IoT), gas sensors have attracted extensive attention in wide-ranging fields such as industrial safety, air pollution monitoring, hazardous substance alert, breath analysis, disease diagnosis, and so on. The development of gas sensors is currently focused on sustainable energy-saving sensors regarding flexible applications. However, with the progress of these key characteristics, attaining a balance among materials, devices, and power consumption is posing more challenges.…”
mentioning
confidence: 99%